“Are you looking for an ambitious job in a fun and international environment?”: Aspects of Employer Branding in Recruitments Advertisements in the Netherlands and in India - Pirttimäki, Ida (My University, 2019)
Recruitment advertisements have been studied and discussed by HR practitioners and academics alike, mostly by scholars coming from fields such as management and business studies, but they have received little attention from linguists. This study connects different aspects related to recruitment advertisements, using linguistic methods to inspect how employer branding is explicitly done in recruitment advertisement from the Netherlands and India. Additionally, it is considered whether what we know about the values of these countries is reflected in the employer branding vocabulary utilized in each country. The main method utilized in this study is keyword analysis (Scott 1997). In the analysis, the corpora of recruitment advertisements from the Netherlands and from India are posited against each other to elicit information about what are the statistical differences in the vocabulary of the corpora. The top keywords from each corpus are then discussed in relation to the textual functions present in the advertisements, such as depicting applicant requirements, describing the role, describing the organization, and of course, employer branding. Additionally, another analysis is performed following the model used by Łącka-Badura (2015) to get an overview of the kind of vocabulary that is used in each country for an employer branding purpose. There are several main findings of this study. As to the keyword analysis, it would appear that at least the top keywords from each corpus are not very closely associated with employer branding. As to the second analysis, the biggest finding is that explicit employer branding is done considerably less in the Indian corpus. There are also qualitative differences as to the vocabulary used in each country. It is then discussed, whether what we know about the values of employment in each country seems to explain any of the differences and tendencies seen in the vocabulary.
Keywords: Keyword analysis, employer branding, cultural values, recruitment advertising